The Fortunes of Pope's 'Essay on man' in 18th-century France - Knapp, R (Voltaire Foundation, 2017)
Preface Introduction I. Background to the Du Resnel and Silhouette translations A. The Voltaire-Du Resnel relationship and the problem of authorship B. The general principles of poetic translation and specifically with regard to the two texts II. The early French reaction to the translations III. Voltaire's reaction to the Essay on man IV. Fontanes's translation and the later French reaction Conclusion List of works consulted